Performance and carcass characteristics of Nellore cattle fed a high-concentrate diet with a phytogenic additive blend - Jéssica Geralda Ferracini; Rodrigo José de Oliveira; Mariana Bassanezi Gasparim; Daniel Polli; Luanda Torquato Feba; Gercino Ferreira Virgínio Júnior; Ivanor Nunes do Prado; Danilo Domingues Millen (PLoS ONE, 2025)
This study evaluated the effects of a phytogenic feed additive – a blend of tannins, flavonoids, and essential oils – on intake, performance, and carcass traits of feedlot-finished Nellore cattle. The additive was hypothesized to enhance performance by modulating ruminal fermentation, favoring more efficient energy utilization pathways. Ninety-six intact Nellore bulls (357.4 ± 25.9 kg) were assigned to 24 pens (4 animals/pen) and fed high-concentrate diets for 116 days. Treatments included: 1) control diet and 2) control plus the phytogenic additive blend. Cattle receiving the phytogenic blend showed a significant reduction in dry matter intake (DMI) as a percentage of body weight (P = 0.04) without changes in final body weight, average daily gain, or carcass ultrasound traits. A numerical improvement in feed efficiency (3.3%; P = 0.19) was observed, along with increased selection for long particles (P = 0.02), potentially indicating altered feeding behavior. No differences were detected in fecal starch content or total starch digestibility. While the phytogenic blend did not significantly enhance performance or carcass traits, the reduction in intake without impairing productivity suggests a potential improvement in feed utilization efficiency. Further research is needed to refine dosing strategies and evaluate their effects under varying feeding conditions.